Digital Pedagogical Transformation in Islamic Education: Deep Learning Integration, Challenges and Solutions - Sicha, Ainus; Rohmana, Devie Wianda; Hidayat, Maulana Wahyu (Proceeding International Conference on Education, 2025)
The digital technology has a significant impact on various sectors, including education. Islamic education, as the moral and spiritual foundation of society, is required to adapt through digital pedagogical transformation. This study aims to examine the integration of deep learning in Islamic education, highlighting its potential, challenges, and potential solutions. This study uses a literature review approach, analyzing various scientific sources, including journals, books, articles, and policy documents related to the application of digitalization in Islamic education. The results indicate that deep learning can improve the effectiveness of the teaching and learning process through interactive, personalized, and critical thinking-based learning. However, several challenges remain, such as limited infrastructure, limited digital competence among educators, and concerns about the displacement of Islamic values in the digital environment. To address these challenges, this study proposes strategies such as technology-based teacher training, the development of a relevant digital curriculum, and the creation of educational content aligned with Islamic values. The integration of deep learning in Islamic education offers significant opportunities for adaptive and visionary pedagogical renewal. In conclusion, digital transformation in Islamic education must be designed holistically and contextually to align with technological developments without neglecting the underlying religious values.